Investigation on the presence and dispersion of thermophilic campylobacter species in broiler carcass parts sold at retail market in konya - Mehmet Halit Minnar; Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
In this study, raw chicken meat pieces are examined for the presence of thermophilic Campylobacter species (C. jejuni, C. coli, C. lari). A total of 120 samples of raw chicken meat pieces (thigh,breast,wing ) were analysed for human consumption sale at Konya market. Campylobacter was isolated from 26 of the thigh, 35 of the breast and 31 of the wing. Total of the 92 positive samples are identified as 24 pieces are C. jejuni (20%), 29 pieces are C. coli (24.17%) and 39 pieces are C. lari (32.5%). According to the data of the research, the proportion of contaminated chicken carcasses with thermophilic Campylobacter spp. was in high levels. It is thought that it is very important tor public health.